Developing Problem-Solving Skills in Students through Instructional Scaffolding - Adebanjo, Salmon Adeyinka; Mohammed, Abidat Oluwashola; Ariyibi, Olanrewaju O. (Asian Journal of Assessment in Teaching and Learning, 2025)
The study examined the use of Instructional Scaffolding in developing problem-solving skills among junior secondary school students in Lagos State, Nigeria. The study employed a quasi-experimental design of pre-test post-test, non-equivalent control group. A multistage sampling technique was first used to sample three schools from the population of all public Junior Secondary Schools students in Lagos State. These three schools had three intact classes of students who were purposively selected as sample for the study which resulted in a sample size of 108 students. Data were then collected using a problem-solving Achievement Test labeled “Junior Secondary School Students Problem-Solving Achievement Test (JSSSPSAT)” and a perception Questionnaire labeled “Junior Secondary School Students Scaffolding Perception Questionnaire (JSSSSPQ)”. The reliabilities of the instruments were computed using Cronbach’s alpha technique, with reliabilities of 0.71 and 0.78 for the JSSSPSAT and JSSSSPQ respectively. The study utilized frequency count, mean, and standard deviation for descriptive analysis and an independent t-test with Two-way ANOVA to test significance at a 0.05 alpha level. The findings revealed that JSS students taught with Teacher-Led-Think-Aloud scaffolding technique were found to significantly perform better than those taught with Reciprocal-Think-Aloud scaffolding (t(106) =13.55, p <0.05). The findings also show that generally, scaffolding strategy is significantly better than conventional teaching method (modified lecture) as students taught under the strategy outperformed those taught under conventional teaching methods (t(66) =4.47, p <0.05), but no significant interaction effect was found between gender and the techniques used [F (2,102) =0.244; p>0.05]. Based on the findings of the study, it was recommended among others that curriculum planners should ensure scaffolding techniques are incorporated into the Junior Secondary School curriculum and whenever a teacher is confronted with the choice of scaffolding technique, Teacher-led-Think-Aloud should be considered over Reciprocal-Think-Aloud scaffolding and gender factors should not be considered when planning and delivering scaffolding strategy lessons.